“If they had a place to live, they would be taking medication”: a qualitative study identifying strategies for engaging street‐connected young people in the HIV prevention‐care continuum in Kenya - Lonnie Embleton; Pooja Shah; Edith Apondi; David Ayuku; Paula Braitstein (Journal of the International AIDS Society, 2023)
Abstract Introduction Street‐connected young people (SCY) experience structural and social barriers to engaging in the HIV prevention‐care continuum. We sought to elicit recommendations for interventions that may improve SCY's engagement along the HIV prevention‐care continuum from healthcare providers, policymakers, community members and SCY in Kenya. Methods This qualitative study was conducted in Uasin Gishu, Trans Nzoia, Bungoma, Nakuru and Kitale counties in Kenya between May 2017 and September 2018 to explore and describe the public perceptions of, and proposed and existing responses to, the phenomenon of SCY. This secondary analysis focuses on a subset of data interviews that investigated SCY's healthcare needs in relation to HIV prevention and care. We conducted 41 in‐depth interviews and seven focus group discussions with 100 participants, of which 43 were SCY. In total, 48 participants were women and 52 men. Results Our analysis resulted in four major themes corresponding to stages in the HIV prevention‐care continuum for key populations. We identified the need for an array of strategies to engage SCY in HIV prevention and testing services that are patient‐centred and responsive to the diversity of their circumstances. The use of pre‐exposure prophylaxis was a biomedical prevention strategy that SCY and healthcare providers alike stressed the need to raise awareness around and access to for SCY. Several healthcare providers suggested peer‐based approaches for engaging SCY throughout the continuum. However, SCY heavily debated the appropriateness of using peer‐based methods. Structural interventions, such as the provision of food and housing, were suggested as strategies to improve antiretroviral therapy adherence. Conclusions This study identified contextually relevant interventions that should be adapted and piloted for use with SCY. Education and sensitization of SCY and healthcare providers alike were identified as possible strategies, along with affordable housing and anti‐poverty strategies as cash transfers and provision of food. Peer‐based interventions are a clear option but require SCY‐specific adaptation to be implemented effectively.